Tinjauan Yuridis Hukum Udara Internasional terkait Jatuhnya Pesawat Tempur Rusia karena Penembakan Turki - Fauziah, Sifa; Masyairna, Ina; Fauzi, Ilham; Kurniawan, Abas; Antoni, Herli (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This issue started when Russian military aircraft entered Turkish airspace during Russia's counter-terrorism operation in Syria, which borders Turkey. The Russian Air Force's Sukhoi Su-24 military aircraft is one of the types of aircraft involved in the incident. Russia's involvement in the Syrian conflict allowed these military aircraft to operate in Syrian airspace. In November 2015, a Russian fighter jet was shot down by Turkey for violating Turkish airspace. Turkey then apologized to Russia, which was well-received. Russia gradually lifted sanctions imposed on Turkey, including the travel ban for Russian citizens wishing to visit Turkey, and allowed Russian tour companies to reopen travel routes to Turkey. In international law, countries are recognized to have equal status and rights, and the right to enforce their jurisdiction or national law only within their own territory. A country's authority is limited to its own territory, whether on land, water, or in the air. A country has the right to regulate people and objects within its territory, based on the principles of territoriality known in international law. Therefore, aircraft must seek permission before crossing the airspace of a country and comply with the applicable regulations during flight.